Introduction Activities Toilet Training for Children Age 5 -6 Years at TK Paud Terpadu Seruni, Malomba Village, Dondo Palu District, Central Sulawesi - Andi Agusniatih; Masita Masita (Budapest International Research and Critics University, 2022)
This study aims to help children increase their success in defecation activities through the introduction ofactivities toilet training. This research was conducted on children aged 5-6 years at the TK PAUD Terpadu Seruni, Malomba Village, Dondo District. The research approach used in this study is a qualitative approach. Data collection techniques were carried out through observation, interviews and documentation. The results of initial observations showed that there were 3 children out of 12 children who had not been able to carry out defecation activities according to the observed indicators. After being given an introduction through toilet training in 9 meetings for 2 weeks, the results of the study showed that the three previously unsuccessful children were able to perform the steps to defecate well.The results of the study were obtained from the observation of the 3 aspects used. First, the cognitive aspect, namely the child knows when it is time to defecate and urinate, the child is able to communicate when he wants to defecate, the child knows the cause of the urge to defecate, the child knows the benefits of defecating, the child knows the steps to defecate, the child can imitate behavior. Such as defecation and urination in the right place, children know the benefits of defecating in place, children know etiquette when entering the toilet or bathroom. Second, the affective aspect, namely the child shows shame if he does not urinate in the toilet, the child is not fussy when urinating in the toilet, the child does not hold back the urge to urinate, the child takes steps to defecate, the child uses the toilet when defecating, the child does toilet etiquette. Third, the psychomotor aspect, namely the child fulfills the aspect of motor readiness, the child can carry out activities after defecation and urination, the child performs etiquette in and out of the toilet correctly. Thus, all children aged 5-6 years who are in TK PAUD Terpadu Seruni, Malomba Village, Dondo District and can carry out defecation activities according to the indicators mentioned above. And it is hoped that parents and teachers will continue to provide supervision of children's defecation activities.